When Zakat is Not Enough: Designing an Islamic Blended Microfinance Model for Asnaf Entrepreneurship - Kamil, Faisal Arief; Said, Muhammad M.; Saharuddin, Desmadi; Hidayah, Nur (Center of Strategic Studies (PUSKAS) BAZNAS, 2026)
PurposeThis study aims to develop an integrated financing model to strengthen the economic empowerment of asnaf in Indonesia and to address structural weaknesses in current zakat-based empowerment practices. Design/Methodology/ApproachThe study uses a qualitative conceptual and comparative approach. It analyzes existing zakat empowerment practices and synthesizes three theoretical frameworks. These frameworks are the microfinance schism between institutionalist and welfarist perspectives, institutional logics, and the Pentahelix collaboration model. FindingsThe study identifies a key paradox. National data show a link between entrepreneurship growth and poverty reduction, yet the share of zakat allocated to productive empowerment declined to 5.1 percent in 2025 Semester 1. Zakat institutions continue to prioritize short-term charitable programs. The main challenges include weak integration between zakat and waqf, limited long-term mentoring, and tension between market efficiency and socio-religious obligations to serve high-risk asnaf. To respond, the study proposes the Islamic Blended Microfinance Model. This model positions zakat and waqf as first-loss capital to absorb risk and enable Islamic microfinance institutions to mobilize commercial financing for asnaf who are currently unbankable. Research limitations/implicationsThe study is conceptual and does not test the model empirically. Future research can apply the model in pilot programs and evaluate its impact on income growth, business sustainability, and graduation from mustahik to muzakki. Practical implicationsThe model offers a clear policy blueprint for BAZNAS, BWI, and Islamic microfinance institutions to shift from charity-based disbursement toward structured capacity-building and risk-sharing financing schemes. Social implicationsThe proposed model strengthens the role of Islamic social finance in sustainable poverty reduction. It supports inclusive entrepreneurship and expands access to financing for vulnerable groups who are excluded from formal financial systems. Originality/valueThis study introduces an original integrative model that connects zakat, waqf, and Islamic microfinance within a blended finance and Pentahelix governance framework. It contributes a new conceptual foundation for aligning Islamic social finance with long-term development and empowerment goals.